A multivariate filter to estimate potential output and NAIRU for the Maltese economy - Brian Micallef (Central Bank of Malta, 2014)
This paper applies a multivariate filter on a small macroeconomic model to derive estimates of Malta's potential output growth, the output gap and NAIRU. These unobservable variables are derived from a system that accounts for the interactions between output, core inflation, unemployment and foreign demand, the latter reflecting the structural characteristics of Malta as a small and open economy. The model is estimated using Bayesian inference methods on quarterly data for the period 1999-2013. The estimates from the multivariate filter are compared with those derived from a univariate filter and production function approaches. The economic and financial crisis of 2009 had a negative impact on Malta's growth potential, although there are tentative signs of a gradual recovery in 2013. On the contrary, the crisis had no permanent impact on NAIRU.
Keywords: E32; E62; H20; H50; 330